Symmetry Switching of Negative Thermal Expansion by Chemical Control - Senn,MS; Murray,C; Luo,X; Wang,L; Huang,F-T; Cheong,S-W; Bombardi,A; Ablitt,C; Mostofi,A; Bristowe,N (Journal of the American Chemical Society, 2016)
The layered perovskite Ca3-xSrxMn2O7 is shown to exhibit a switching from a material exhibiting uniaxial negative to positive thermal expansion as a function of x. The switching is shown to be related to two closely competing phases with different symmetries. The negative thermal expansion (NTE) effect is maximised when the solid solution is tuned closest to this region of phase space but is switched off suddenly on passing though the transition. Our results show for the first time that, by understanding the symmetry of the competing phases alone, one may achieve unprecedented chemical control of this unusual property.